Improving the care of patients with a hip fracture: a quality improvement report. Issue 8 (15th May 2015) - Hawkes, David; Baxter, Jonathan; Bailey, Claire; Holland, Gemma; Ruddlesdin, Jennifer; Wall, Alun; Wykes, Philip
Abstract : Introduction: Hip fractures are associated with high rates of morbidity and mortality and their incidence is set to increase. The National Hip Fracture Database and the Best Practice Tariff were introduced with the aim of improving patient care. This complete audit cycle charts the substantial clinical improvements that were achieved in a busy district general hospital. Methods: The first audit cycle comprised 379 patients who were admitted between May 2012 and April 2013. The primary audit criterion was operative intervention within 36 h of admission. Variation according to the day of the week of admission was assessed to evaluate specific deficiencies in local service provision. The principle audit intervention was the introduction of two additional morning trauma lists. A re-audit of 162 patients was conducted prospectively between January 2014 and June 2014. Results: Mean time to theatre was 49±39 h during the first audit cycle compared with 27±19 h (p<0.0001) during the second. Consequently, the proportion of patients undergoing operative intervention within 36 h of admission improved from 41% to 78% (p<0.0001). Overall achievement of Best Practice Tariff was significantly higher during the second cycle: 28% vs 73% (p<0.0001). Conclusions: Significant improvements in the quality of hip fracture care were achieved following this audit. These were accomplished by rigorously analysing the variation in Best Practice Tariff achievement according to the day of the week on which patients were admitted. Targeted interventions could therefore be introduced that addressed specific problems in local service provision.